Exploring the Integration of Massive Open Online Courses in Social Sciences at Universities in Delhi: A Librarian’s PerspectivesA Librarians Perspectives - Bhardwaj, Raj Kumar (DESIDOC Journal of Library & Information Technology, 2025)
The study aims to understand the integration of massive open online courses (MOOCs) in social sciences in Indian universities. Therefore, the present study comprehends the awareness of librarians on MOOCs in social sciences and their perspectives on the integration of MOOCs in formal education. The responses were received from senior library professionals at universities in Delhi, and their responses were analysed and presented in tables and figures. The study found that 85.71 % of respondents from universities stated MOOCs enhance the knowledge of learners. Besides this, 71.43 % of librarians consider MOOCs are found self-effective and also help in self-assessment. Furthermore, 71.43 % of librarians revealed the integration of MOOCs with formal education is required. And, 71.43 % of librarians opined that MOOC courses are a time-consuming process. Interestingly, 100 % of respondents expressed that MOOCs are flexible, useful and supplement to academic and professional growth. All respondents agree that learning concepts are easy in MOOCs. The study also found that accredited MOOCs stretch the learners’ capabilities and 85.7 % of respondents expressed that the user interface of the MOOCs are well designed and easy to navigate and functions well. Furthermore, found that MOOCs enhance professional development and career progression for employees, improving the curriculum. All respondents under study are aware of the Indian Copyright Act 1957 and related amendments